A Rare Case of Methylprednisolone-Induced Exogenous Cushing’s Syndrome - Muddapur, Ramkumar L (Journal of Pharmacy Practice and Community Medicine)
Exogenous corticosteroid use is a well-recognized cause of iatrogenic Cushing syndrome. Among systemic glucocorticoids, methylprednisolone is widely prescribed for inflammatory and autoimmune conditions. Corticosteroids, naturally produced by the adrenal cortex or synthetically formulated, play a vital role in various medical treatments. Glucocorticoids, such as methylprednisolone and hydrocortisone, possess potent anti-inflammatory, immunosuppressive, anti-proliferative and vasoconstrictive properties, making them essential in controlling inflammatory diseases. This case report discusses 65-year-old male patient with history of Rheumatoid Arthritis managed with long term methylprednisolone use 4 mg BD for 2 years presenting with cough with expectoration, breathlessness, wheezing, lower limb swelling and abdominal pain. Clinical evaluation found to be normal. His treatment includes nebulized bronchodilators (levosalbutamol and ipratropium bromide), corticosteroids (budesonide), antibiotics (Piperacillin-tazobactum, clarithromycin) and supportive therapy with oxygen. This case underscores the importance of carefully monitoring corticosteroid therapy to prevent adverse effects. A balanced approach in steroid administration is crucial to minimizing complications while maximizing therapeutic benefits.
Keywords: Corticosteroids; Cushing’s syndrome; Immunosuppressive; Methylprednisolone